PENINGKATAN RESILIENSI PENGASUHAN MATERNAL PADA IBU DENGAN ANAK RISIKO STUNTING BERBASIS EDUKASI GIZI DIGITAL - Rachmawaty M. Noer; Husaini; Wulan Pramadhani (LPPM Universitas Awal Bros, 2026)
​​ Stunting is a chronic nutritional problem that remains a major concern in public health, especially in toddlers. One factor that plays a role in preventing stunting is the mother's ability to provide good care, including an understanding of child nutrition. Nutrition education is one effort that can be done to improve mothers' knowledge and abilities in child care. This study aims to determine the effect of nutrition education through video media on maternal care resilience in mothers with children at risk of stunting in the work area of ​​the Tambelan Community Health Center UPTD, Bintan Regency. This study used a pre-experimental design with a one-group pretest-posttest approach. The population in this study were mothers with children at risk of stunting with a sample of 32 respondents selected using the total sampling technique. Data collection was carried out using a maternal care resilience questionnaire administered before (pretest) and after (posttest) the nutrition education intervention through video media. Data analysis was performed using the Paired Sample t-test after a normality test using Shapiro-Wilk. The results of the study showed that the average value of maternal care resilience before the intervention (pretest) was 96.91, while after the intervention (posttest) it increased to 111.75. The results of the statistical test showed a p-value = 0.000 (p <0.05) which means there is a significant effect of nutrition education through video media on increasing maternal care resilience in mothers with children at risk of stunting. The conclusion of this study shows that nutrition education through video media is effective in increasing maternal care resilience. Therefore, video media can be used as a method of health education in efforts to prevent stunting in the community, especially for mothers who have children at risk of stunting.